Alternate wetting and drying (AWD) in Burkina Faso for water saving without a yield penalty - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Using a participatory approach, AWD was successfully validated in 4 sites characterized by different soil and climate conditions in the dry and wet seasons in Burkina Faso. Suitable domains for large-scale dissemination of AWD were identified using the ecological niche modeling approach.